Enhanced inflammation and attenuated tumor suppressor pathways are associated with oncogene‐induced lung tumors in aged mice. Issue 1 (18th October 2017) - Parikh, Neha; Shuck, Ryan L.; Gagea, Mihai; Shen, Lanlan; Donehower, Lawrence A.
Summary: Aging is often accompanied by a dramatic increase in cancer susceptibility. To gain insights into how aging affects tumor susceptibility, we generated a conditional mouse model in which oncogenic Kras G12D was activated specifically in lungs of young (3–5 months) and old (19–24 months) mice. Activation of Kras G12D in old mice resulted in shorter survival and development of higher‐grade lung tumors. Six weeks after Kras G12D activation, old lung tissues contained higher numbers of adenomas than their young tissue counterparts. Lung tumors in old mice displayed higher proliferation rates, as well as attenuated DNA damage and p53 tumor suppressor responses. Gene expression comparison of lung tumors from young and old mice revealed upregulation of extracellular matrix‐related genes in young tumors, indicative of a robust cancer‐associated fibroblast response. In old tumors, numerous inflammation‐related genes such as Ccl7, IL‐1 β, Cxcr6, and IL‐15ra were consistently upregulated. Increased numbers of immune cells were localized around the periphery of lung adenomas from old mice. Our experiments indicate that more aggressive lung tumor formation in older Kras G12D mice may be in part the result of subdued tumor suppressor and DNA damage responses, an enhanced inflammatory milieu, and a more accommodating tissue microenvironment.